Application of Kalman filtering based on sequential processing for satellite navigation - Can-hui CHEN; Xiao-lin ZHANG; Hang-yu HUO (Tongxin xuebao)
In order to reduce the operational volume and ensure the real-time capability of navigation algorithm of Kalman filtering,a novel filtering method called single-satellite sequential extended Kalman filtering (S3EKF) was proposed based on extended Kalman filtering (EKF) and sequential processing,where the single-satellite was as basic filtering unit.Simulation results show that,compared with the traditional EKF method,the S3EKF method can decrease the computation load efficiently when the number of visible satellites is no less than 7,and the reduction of computation load increases with the increase of the satellite’s visible n r,the decrease will reach more than 50% when the number of visible satellites is no less than 15.On the other hand,the consistency and stability of navigation solution are good when the satellites and their number are time-vraiant in S3EKF method.